EFEKTIVITAS MODEL PEMBELAJARAN JIGSAW PADA KETERAMPILAN MENULIS BAHASA PERANCIS - Hardini, Tri Indri; Karimah, Iim Siti; Erliani, Adelya (Jurnal Pendidikan Bahasa dan Sastra, 2020)
This research aims to describe studentâ€™s writing ability before and after using Jigsaw model, the effectiveness of Jigsaw model in improving writing skills, and the opinion of students. This study applies descriptive quantitative method in form of pre-experimental design. Instruments that are used in the form of tests and questionnaires. The sample of this research is 32 characteristics writing skill of 6thÂ  semester French Education students. Based on the research result, the researcher can conclude that the students have been able to write the argumentative text nicely. The test result showed that the average test score after using the Jigsaw model is 8.9. It means, the average posttest score is higher than the average pretest score, up to 1.7%. Meanwhile, the results of the questionnaire show that students like writing but they find so much difficulty in making a writing or a text, and most students give a positive impression for the Jigsaw model.